國小教師參與數學補救教學培育課程自我覺知數學教學知識改變之研究 Elementary School Teachers' Awareness of their Changes in Mathematics Pedagogical Content Knowledge after Attending Mathematics Remedial Instruction Courses - 蕭芷芸 Jhih-Yun Siao; 陳彥廷 Yen-Ting Chen; 陳中川 Chung-Chuan Chen (National Changhua University of Education, 2017)
本研究旨在探究兩位國小教師在進行數學補救教學培育課程前、後，自我覺知數學教學知識的改變及其在實踐數學補救教學時，所呈現的數學教學知識整合樣貌。首先，研究者提供「國小教師數學教學知識知覺量表」與問卷給予兩位教師評估自身之數學教學知 識現況；其次，再以他們進行「整數四則混合計算」與「周長與面積」等兩個單元之數學補救教學錄影資料，分析其數學教學知識的整合情形；最後，根據兩位教師在數學補救教學培育課程前、後所填寫之量表與問卷，分析他們自我覺知數學教學知識的改變， 以及數學補救教學培育課程對其數學教學知識的影響。研究結果顯示：1. 兩位教師在培育課程前，對自身數學教學知識之知覺存在差異；2. 兩位教師經過數學補救教學培育課程後，自覺數學教學知識各面向皆有成長；3. 兩位教師在實踐數學補救教學中，其展現 的數學教學知識整合亦具有一致性；4. 兩位教師經過數學補救教學培育課程後，更保守地評估自己的數學補救教學知識，其對於數學教學知識的自覺呈現一致性。 Focusing on two participating elementary school teachers, this study investigated the selfawareness of their changes in mathematical pedagogical content knowledge after attending mathematics remedial instruction courses. This study also examined the overall performances of their mathematical pedagogical content knowledge when they engaged in mathematics remedial instruction practices. First, the researchers presented the teachers with a questionnaire on "Selfperception of Mathematics Pedagogical Content Knowledge for Elementary School Teachers" in order to assess their mathematical pedagogical content knowledge prior to the study. Second, based on videotape recordings during their classroom teaching of two math remedial units on "the four fundamental operations of integers" and "perimeter and area", the researchers analyzed the extent as to how well the teachers were able to successfully integrate different components of mathematical pedagogical content knowledge into their teaching practices. Finally, the teachers' awareness of their changes in mathematical pedagogical content knowledge was analyzed from the results of the questionnaires they took before and after attending the mathematics remedial instruction courses. Impacts of the mathematics remedial instruction courses on the teachers' mathematical pedagogical content knowledge were also explored. The results indicate that differences do exist between the two teachers' self-perceptions of mathematical pedagogical content knowledge before attending the mathematics remedial instruction courses. In addition, after attending mathematics remedial instruction courses, both participating teachers improved their mathematical pedagogical content knowledge. Moreover, it is noted that the two teachers demonstrated quite similar overall performances in combining the various components of mathematical pedagogical content knowledge during their mathematics remedial instruction practices. After attending the mathematics remedial instruction courses, both teachers tended to assess their pedagogical knowledge in mathematics remedial instruction more cautiously and also showed similar and consistent self-awareness of their changes in mathematical pedagogical content knowledge.